Austria : Selected Issues. (IMF Staff Country Reports; Country Report, 2013)
This paper focuses on Austria's 2013 Article IV Consultation on economic development and policies related to labor demand and supply. Austria taxes labor heavily, and this practice explains in particular the limited labor supply of low-skilled workers and women. The IMF report highlights that social security contributions and payroll taxes amount to almost 50 percent of gross monthly wages. It analyzes that a comparatively high share of Austria's family benefits is monetary rather than in kind. Work incentives for low-skilled workers could be strengthened by selectively lowering social security contributions and/or payroll taxes, and reducing the entry income tax rate.